Efektivitas Taping pada Ekstremitas Bawah Terhadap Performa Change Of Direction pada Pemain Sepak Bola: Systematic Literature Review - Nisrina Aulia Nurutami; Sri Novia Fauza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to evaluate the effectiveness of taping on change of direction (CoD) performance in soccer players using a systematic literature review (SLR) approach. The method followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines, with literature searches conducted in Scopus, PubMed, and Google Scholar databases from 2010 to 2026. Article selection was performed using the PICOS framework, resulting in eight eligible studies. The findings indicate that most studies reported improvements in agility performance related to CoD following the application of taping, although some studies found no significant differences. The types of taping applied included kinesio taping, neuromuscular taping, and dynamic taping, primarily on lower extremity muscles such as the quadriceps and gastrocnemius. These improvements are associated with enhanced proprioceptive stimulation and joint stability. In conclusion, taping has potential as a complementary intervention to improve change of direction (CoD) performance; however, its effectiveness remains inconsistent due to variations in application techniques, duration, and subject characteristics. Therefore, taping is more effective when combined with structured physical training programs rather than being used as a primary intervention. Keywords: Agility, Change of Direction, Soccer, Taping